Pembiayaan Bermasalah pada Bank Muamalat Indonesia: Apakah Faktor Internal dan Faktor Eksternal Berpengaruh? - Noviatul Fitriya; Mochamad Edman Syarief; Anhar Firdaus (Journal of Applied Islamic Economics and Finance, 2022)
The purpose of this study was to find out the effect of the ratio of Operating Costs and Operating Income (BOPO), Capital Adequacy Ratio (CAR), Financing to Deposite Ratio (FDR), Inflation, and Exchange Rate (Exchange Rate) on Non Performing Financing (NPF) at Banks. Sharia Muamalat. The population used in this study is Bank Muamalat Indonesia and the data used is time series data sourced from the quarterly reports of Bank Muamalat Indonesia for the 2011-2020 period published on the bank's official website. The method used to solve this problem is to use quantitative research with multiple regression analysis and is supported by Eviews9 software as an application to process data. The findings of this study are to contribute to Bank Muamalat Indonesia regarding the factors that affect the NPF at Bank Muamlat Indonesia.